Pemberdayaan Masyarakat UMKM di Era Digital Melalui Kegiatan KKN Desa Sitiwinangun - Sari, Rafika; As-Sanaj, Tyathanesia Dianfitri; Pranoto, Imam Aji; Setiawan, Dwi Adi; Adesta, Fillah Akhyar Rezqi; Umam, Ibni Khoerul; Ardan, Raditia Muhammad; Danu, Julian Firman; Ningrum, Citra Urba (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The ability to adapt processes in the transformation from the conventional marketing era to the digital marketing era requires knowledge of digital literacy. How to utilize digital media and what strategies are needed to improve product marketing is absolutely a must have for today's business actors. Based on this, the Kuliah Kerja Nyata (KKN) activities try to bridge the increase in digital literacy in the UMKM community. The partners in this KKN activity are in the Sitiwinangun Village community, Kabupaten Cirebon. This village has one of the regional specialties of pottery handicrafts which has not utilized technology in marketing its products. Indicators of successful implementation of this KKN work program are: suitability of work program plans and implementation, level of community participation in each activity, and increasing knowledge of the UMKM community in Sitiwinangun Village regarding digital literacy in product marketing. Some of the outputs produced through this community service KKN activity, namely: increasing the hard skills of UMKM actors in making good and interesting product videos, increasing digital literacy for local youth, making village profile videos that have been published on YouTube social media, and decorate creative trash bins as a form of environmental care campaign.